Efficacy and safety of henagliflozin combined with continuous subcutaneous insulin infusion in the treatment of Chinese inpatients with type 2 diabetes mellitus based on a continuous glucose monitoring system: protocol of a multicentre, open-label, inpatient, randomised, controlled trial - Yingfen Qin; Yingling Wu; Zhenxing Huang (BMJ Open)
Introduction The role of sodium-glucose cotransporter 2 inhibitors (SGLT2is) in diabetes treatment is expanding; however, few studies have investigated the efficacy and safety of combining SGLT2is with insulin pump therapy. Notably, there is a scarcity of high-quality, multicentre, clinical trials. Therefore, we aim to conduct a prospective multicentre, randomised, controlled, study to investigate whether treatment of type 2 diabetes patients with continuous subcutaneous insulin infusion (CSII) combined with henagliflozin can reduce the time required for blood glucose control, decrease total insulin requirements, mitigate blood glucose fluctuations and enhance beta-cell function.Methods and analysis In this inpatient, open-label, multicentre, randomised, controlled trial, 200 patients with type 2 diabetes who have not received hypoglycaemic drugs will be randomly allocated at a 1:1 ratio to either the henagliflozin combined with CSII group or the CSII group. The efficacy and safety of treatment in both groups will be compared. We will use a real-time continuous glucose monitoring system for blood glucose monitoring. The primary aim of this study is to compare the time (% time in range (TIR)) in the range of 3.9~10.0 mmol/L blood glucose between the two treatment groups. The secondary outcome measures will include comparisons of the two treatment groups with respect to the (a) time at TIR >70%; (b) mean amplitude of glycaemic excursions; (c) time below range; (d) total insulin dosage; and (e) time above range.Ethics and dissemination This study was approved by the Ethics Committee of the First Affiliated Hospital of Guangxi Medical University and is to be conducted in accordance with the Declaration of Helsinki and Good Clinical Practice. The study will be disseminated through peer-reviewed publications and conference presentations.Trial registration number NCT05677334.